PENGARUH LATIHAN PATHNER RESISTED STAR TERHADAP KECEPATAN PEMAIN FUTSAL CLUB KELAMBIR 38 PEKANBARU - Rifai, Muhammad; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the above description in futsal players the running speed of a soccer player is also very influential for attack and defense. Whereas Based on observations in the field, it can be seen that there are many players at the Kelambir 38 Pekanbaru club who lack the running speed when carrying out attacks and when defending so that the defeat often sprints clash the ball with the opposing players. The purpose of this study was to determine the effect of pathner resisted start training on the speed of Club Kelambir 38 futsal players in Pekanbaru. The population in this research were 12 Club Kelambir futsal athletes in Pekanbaru. The sampling technique is saturated sampling, namely the technique of determining the sample if all members of the population are used as samples, then the sample in this study was set at 12 people. The instrument in this study was a 30 meter running speed. Based on data analysis and discussion, it can be concluded that there is an effect of pathner resisted start training on the speed of Club Kelambir futsal players 38 Pekanbaru as evidenced by the results of tcount 14,241> t table 1.796 at α = 0.05. This proves that by doing a start resisted pathner exercise, the speed can get better results.Key Words; Pathner Resisted Start, Speed.